ANALISIS BENTUK DAN RUANG PADA RUMAH MELAYU TRADISIONAL DI KOTA SAMBAS KALIMANTAN BARAT - Zain, Zairin (Nalars, 2012)
ABSTRAK. Arsitektur rumah Melayu tradisional di kota Sambas juga merupakan unsur kebudayaan nasional yang mempunyai struktur, fungsi dan style dengan bentuk fisik dalam proses pembuatannya senantiasa memberikan karakteristik tersendiri. Arsitektur tradisional sebagai hasil karya, cipta, karsa dan rasa manusia sebagai unsur kebudayaan manusia, yang tidak lepas dari interaksi dan pemahaman antara lingkungan fisik alam sekitar dengan keahlian atau kemampuan masyarakat dalam membentuk suatu kognisi. Penelitian ini dilakukan terhadap 3 (tiga) kasus rumah tradisional yang dijadikan sebagai kasus penelitian. Lokasi ketiga kasus tersebut terletak di kampung Dalam Kaum sebanyak 1 (satu) rumah Potong Kawat (kasus II) dan kampung Tanjung Mekar sebanyak 2 (dua) buah rumah yaitu potong Limas (kasus I) dan Potong Godang (kasus III). Kedominanan bentuk yang diberikan pada rumah tinggal Melayu tradisional baik secara vertikal maupun horizontal pada elemen pembentuk fasad disusun untuk memberikan perlindungan total dan kebebasan bagi anggota keluarga; sedangkan susunan ruang pada rumah Melayu tradisional di kota Sambas diarahkan pada penggunaan ruang secara bersamaan agar dapat menampung orang dalam jumlah yang banyak. Kata kunci : rumah Melayu tradisional, bentuk, ruang, kestabilan struktur ABSTRACT. The architecture of traditional Malay houses in the town of Sambas is also an element of the national culture and they also owned structure, function and style with the form, in its development process, is physically continues to provide its own characteristics. The traditional architecture as a result of the work, creativity initiative and the sense of man is an element of human culture, which can not be separated from the interaction and the understanding of the natural and physical environment with the skill or ability of the communities to form a cognition. The research was conducted on 3 (three) cases of the traditional Malay houses that serve as cases on this study. Three cases and its location site which were choosed as samples is in the following: 1 sample in the village of Dalam Kaum for Potong Kawat or the Kawat shape (as case II) and 2 samples were choosen in the village of Tanjung Mekar for Potong Limas or the Limas shape (as case I) and PotongÂ Godang or Godang shape (as case III). The dominance is given by the form of traditional Malay houses, either vertically or horizontally, on the facade is forming the element arrangement to provide the total protection and freedom for all family members, whereas the spatial arrangement of the traditional Malay houses in the town of Sambas is directed to the use of space at the same time in order to accommodate many people in large numbers for traditional ceremony.Keywords : traditional Malay houses, forms, space, stability of the structureÂ